The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jdeveco.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of opportunity and growth

Abstract: Theoretical models and empirical studies exploring the relationship between income inequality and growth reach a disappointing inconclusive answer. We postulate in this paper that one reason for this inconclusive result is that income inequality consist at least in two different sorts of inequality, inequality of opportunity and effort. These two types of inequality would affect growth through opposite channels. As a result, the relationship between income inequality and growth could be positive or negative de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
5
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 79 publications
(49 reference statements)
7
129
5
8
Order By: Relevance
“…While this weak finding is neither robust to changes in specification nor to switching to the DHS data set, it is nonetheless inconsistent with a positive association such as the one found by Forbes (2000) and Li and Zou (1998). Furthermore, we find no evidence in support of our original hypothesis, which found some support in a data set of 26 U.S. states (Marrero and Rodríguez, 2013): there is no apparent relationship between either component of inequality and growth in either of our two data sets.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While this weak finding is neither robust to changes in specification nor to switching to the DHS data set, it is nonetheless inconsistent with a positive association such as the one found by Forbes (2000) and Li and Zou (1998). Furthermore, we find no evidence in support of our original hypothesis, which found some support in a data set of 26 U.S. states (Marrero and Rodríguez, 2013): there is no apparent relationship between either component of inequality and growth in either of our two data sets.…”
Section: Discussioncontrasting
confidence: 99%
“…Table A3 confirms these null findings when the instrument set is restricted further using the pca option. These findings are clearly not supportive of the hypothesis that there might be a negative association between inequality of opportunity and growth (and a positive one between the residual inequality and growth) à la Marrero and Rodríguez (2013).…”
Section: Estimation and Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…However, the paper acknowledges that its empirical analysis "is not very informative regarding the different channels through which inequality might affect income." 8 The closest study we found is Marrero and Rodriguez (2010). In line with our results, they find opposing effects for inequality of opportunities and for inequality of returns.…”
Section: Empirical Approachsupporting
confidence: 84%
“…In contrast, inequality of returns to efforts gives incentives to households to work harder. The conventional view is correct with respect to inequality of returns to efforts as it increases an economy's growth rate; however inequality of opportunities decreases it (Marrero and Rodríguez, 2013). High levels of inequality of opportunity are usually coupled to low social mobility, a fact which is also known as the 'Great Gatsby Curve' (Corak, 2013).…”
Section: Does Inequality Reduce Economic Efficiency?mentioning
confidence: 99%